2017
DOI: 10.1086/693856
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Association Predicts Genetic Diversity and Population Divergence in Amazonian Birds

Abstract: The ecological traits of organisms may predict their genetic diversity and population genetic structure and mediate the action of evolutionary processes important for speciation and adaptation. Making these ecological-evolutionary links is difficult because it requires comparable genetic estimates from many species with differing ecologies. In Amazonian birds, habitat association is an important component of ecological diversity. Here, we examine the link between habitat association and genetic parameters usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 118 publications
(133 reference statements)
4
90
4
2
Order By: Relevance
“…Previous studies have emphasized the role of biological attributes in the idiosyncratic responses of different species to shared environmental changes, even between codistributed taxa (Garg et al, ; Prates, Rivera, Rodrigues, & Carnaval, ; Prates, Xue et al, ; Smith et al, ). It has been shown that differences in habitat choice and ecological constraints can explain variation in the levels of population divergence across taxa (Burney & Brumfield, ; Garg et al, ; Harvey et al, ; Smith et al, ; Weir, Bermingham, & Schluter, ). In particular, this has been linked to differential dispersal abilities: forest specialists and understorey birds have poor dispersal abilities (Moore, Robinson, Lovette, & Robinson, ) and are less likely to move across a barrier, while habitat generalists, canopy birds and species that inhabit open environments show a higher dispersal propensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have emphasized the role of biological attributes in the idiosyncratic responses of different species to shared environmental changes, even between codistributed taxa (Garg et al, ; Prates, Rivera, Rodrigues, & Carnaval, ; Prates, Xue et al, ; Smith et al, ). It has been shown that differences in habitat choice and ecological constraints can explain variation in the levels of population divergence across taxa (Burney & Brumfield, ; Garg et al, ; Harvey et al, ; Smith et al, ; Weir, Bermingham, & Schluter, ). In particular, this has been linked to differential dispersal abilities: forest specialists and understorey birds have poor dispersal abilities (Moore, Robinson, Lovette, & Robinson, ) and are less likely to move across a barrier, while habitat generalists, canopy birds and species that inhabit open environments show a higher dispersal propensity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent comparative studies show that phylogeographical patterns shared among codistributed taxa divided by the same barrier cannot be explained only by a common vicariant event (Brumfield, 2012;Naka & Brumfield, 2018;Oswald et al, 2017;Smith et al, 2014). Instead, evolutionary histories are idiosyncratic and depend largely on the biological attributes of species, such as ecology and dispersal ability, resulting in different and asynchronous responses to a shared evolutionary driver (Burney & Brumfield, 2009;Garg, Chattopadhyay, Wilton, Malia Prawiradilaga, & Rheindt, 2018;Harvey, Aleixo, Ribas, & Brumfield, 2017;Smith et al, 2014).…”
mentioning
confidence: 99%
“…With the advent of modern DNA genotyping techniques, studies investigating thousands of genetic markers from across the genome are becoming more common (Gaughran et al, 2018;Hand et al, 2015;Harvey, Aleixo, Ribas, & Brumfield, 2017;Hudson, Freeman, Myburg, Potts, & Vaillancourt, 2015), and several studies have investigated patterns of nuclear genetic structure and gene flow across large geographic regions (Hecht, Matala, Hess, & Narum, 2015;Hendricks et al, 2017;Sampson et al, 2018;Shriver et al, 2005). Studies such as these provide critical information for the conservation of populations with unique genetic heritage, identification of areas of adaptive potential for assisted migration and location of source populations or historical refugia (Hecht et al, 2015;Supple et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to population contraction and fragmentation during the Pleistocene in Savannah sparrows is consistent with several hypotheses that link ecological and life history attributes to patterns of population genetic differentiation. First, certain habitat associations can influence patterns of genetic structure with species that occupy more open and/or ephemeral habitats exhibiting less genetic structure than forest/closed habitat species (e.g., Burney & Brumfield, ; Drovetski, Zink, Ericson, & Fadeev, ; Harvey, Aleixo, Ribas, & Brumfield, ). One hypothesis explaining this pattern is that open country taxa exhibit increased dispersal propensity to exploit ephemeral or patchy resources (e.g., Burney & Brumfield, ).…”
Section: Discussionmentioning
confidence: 99%